Full House: A Retrospective Analysis of High Sexually Transmitted Infection Prevalence among Adult Film Actors at a Singular Residence. Issue 9 (September 2016) - Kendrick, Katherine; Brown, Veronica; Lords, Caleb; Matthias, James; Henning, Ian; Blackmore, Carina; Likos, Anna
Abstract : Background: During a routine human immunodeficiency virus (HIV) investigation, Florida Department of Health staff identified a house (house A) in which over 150 individuals had resided at least briefly. Further investigation revealed that house A is used by the producer of a small adult film production company to board his actors. This report describes sexually transmitted infection (STI) prevalence among male actors in gay adult films residing in a common Florida residence. Methods: LexisNexis Accurint was used to identify house A residents since October 2002 when the producer arrived. Information on STIs and interview data were obtained from Florida's STI surveillance system. An infection was considered to be associated with residence in house A if the date of diagnosis occurred 6 months before an individual's residence start date through 6 months after his residence end date. Results: Excluding the producer, 150 men resided in house A starting from September 2003 to July 2015. Forty-six individuals had a reported case of HIV, syphilis, gonorrhea, and/or chlamydia with 92 infections total. Forty-two (46%) infections among 24 men were considered associated with residence in house A. Conclusions: LexisNexis Accurint was a useful tool for identifying house A residents, a highly mobile and highly sexually active population. There is a high prevalence of STIs among residents, but it is unclear where transmission is occurring. Settings like house A are good candidates for HIV pre-exposure prophylaxis and active STI screenings and may be an opportunity for public health officials to intervene in high-risk groups to reduce STI rates in the community. Abstract : This report describes sexually transmitted infection prevalence among male actors in gay adult films with evidence of residence at a singular location in Florida.